THE ELDERLY IN TWO ADVERTISING: A DISCURSIVE ANALYSIS - Bazza, Adelli Bortolon; Torquette, Akisnelen de Oliveira [UNESP] (Univ Estadual Oeste Parana-unioeste, 2015)
The advertisements are a discursive genre that are meant to promote a brand, product or service attracting investors and / or customers. Its constitution strategies are varied: ranging from humor to the controversy. This feature allows each advertisement reaches the public in a different way, generating empathy, moving reviews, discussions etc. Because of this social relevance, this study aims to analyze two advertisements of Havaianas sandals, aired on television and the internet, in the months of August and September 2009. These pieces had as main character an elderly: (i) in the first interaction situation with his granddaughter; and (ii) the second to the viewer. In the latter, referred to the answer given by the public on the contents of the first piece. The interest in these parts is related to the controversy generated about the old character and his speech. From the interactionist perspective, based on the conceptual framework of Bakhtin and his Circle, proposes to examine the discursive process initiated by the enunciation of these parts in order to describe elements rooted in shared social knowledge about the elderly. Thus, we mobilized the concepts of dialogism, interaction and axiological concepts of discourse. The analysis of the specimens shows that the representation of the elderly as a partner responsible for a more liberal discourse on emotional and sexual life is not yet part of the social horizon of the Brazilian public. His appearance generates dialogue with the public (albeit to receive criticism) that concerns this brand interactions.
Keywords: interaction; advertising; aged